2013
DOI: 10.4000/quaternaire.6843
|View full text |Cite
|
Sign up to set email alerts
|

Après le Déluge : évolution géomorphologique du delta du Danube après la reconnexion Mer Noire - Méditerranée et ses implications sur le peuplement énéolithique / Chalcolithique

Abstract: Ce document est un fac-similé de l'édition imprimée. © Tous droits réservés

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Elemental determinations were performed using energy dispersive X-ray fluorescence (ED-XRF) to gain insight into the mineralogic composition of the sediments. Analyses were performed using a portable Bruker Tracer S1 Titan spectrometer, that Carozza et al, 2013;KP1 and KP2 in Filip and Giosan, 2014;F16 and F18 in Vespremeanu-Stroe et al, 2017) are indicated by yellow squares. The dashed line with the L5 mark (Vespremeanu-Stroe et al, 2016) indicates the boundary between longshore and fluvial borne sediments.…”
Section: Xrf Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Elemental determinations were performed using energy dispersive X-ray fluorescence (ED-XRF) to gain insight into the mineralogic composition of the sediments. Analyses were performed using a portable Bruker Tracer S1 Titan spectrometer, that Carozza et al, 2013;KP1 and KP2 in Filip and Giosan, 2014;F16 and F18 in Vespremeanu-Stroe et al, 2017) are indicated by yellow squares. The dashed line with the L5 mark (Vespremeanu-Stroe et al, 2016) indicates the boundary between longshore and fluvial borne sediments.…”
Section: Xrf Analysismentioning
confidence: 99%
“…OSL dating was performed at the Luminescence and Gamma Spectrometry Laboratory (LEGaL), Institute of Geosciences of the University of São Paulo (USP). After the 180-250 µm grainsize fraction was isolated and organic matter, carbonates, heavy minerals, and feldspars were removed following standard Carozza et al, 2013), KP1 and KP2 (Filip and Giosan, 2014), and F16 and F18 (Vespremeanu-Stroe et al, 2017).…”
Section: Absolute Datingmentioning
confidence: 99%
See 1 more Smart Citation
“…Core 10. Sedimentological analysis has been focused on core 10, on which laser grain-size (Coulter Beckman 200), geochemical (XRF, AVAATECH) analyses and Magnetic Susceptibility (Bartington MS2E) have been carried out (Carozza et al, 2013). This core (Fig.…”
Section: Coring Core Description and Datingmentioning
confidence: 99%
“…This core (Fig. 3) can be subdivided into four main units (see Carozza et al, 2013): 1) from 300 to 259 cm (US1), fine pale brown sediments of massive structure that were interpreted as loess and palaeosoil developed on loess; from 259 to 153 cm (US2), alternated dark silt and clay were interpreted as fluviolacustrine deposits, consistent with the faunal remains (shells and fishbones); from 153 to 108 cm (US3), the deposit is a more homogeneous clay-silt organic layer; the top of the core (US4a and b) is composed of an alternation of clay-silt and sandy levels, indicating a fluvial (and more dynamic) origin.…”
Section: Coring Core Description and Datingmentioning
confidence: 99%